IMPLEMENTASI MANAJEMEN PEMBELAJARAN UNTUK MENINGKATKAN MUTU SEKOLAH DI SDIT PERMATA HATI JAYAPURA - Ayomi, Bekti Nur; Hidayati, Dian; Sukirman, Sukirman (STKIP Pesisir Selatan, 2026)
Integrated Islamic Schools (SIT) offer a model of education based on Islamic values, integrating the national curriculum with a unique Islamic curriculum that reflects the school's vision and mission of developing a rabbani generation. In practice, they not only provide general knowledge but also instill Islamic values in every subject as part of the holistic and integrated development of students' personalities. Learning methods optimize the cognitive, affective, and psychomotor domains through their learning methods. However, various challenges arise in its implementation, such as limited teacher numbers due to high teacher mobility, varying teacher abilities, and difficulties in aligning the general curriculum with the school's unique curriculum, specifically the integration of Islamic values in an applicable and contextual manner. These conditions can directly impact the quality of the learning process and outcomes if not managed effectively. Therefore, effective and well-planned learning management is crucial to improving student learning outcomes and optimally achieving the school's educational vision and mission. This study aims to analyze learning management strategies in an effort to develop school quality at Integrated Islamic Elementary Schools (SDIT).